Study on the electronic structures of the reduced anatase TiO2 by the first-principle calculation - Cheng, Z.; Liu, T.; Yang, C.; Gan, H.; Zhang, Feiwu; Cheng, J. (Pergamon, 2012)
Employing the first-principle calculations based on the density functional theory (DFT) and the Molecule Orbital theory (MO), we have researched the electronic structures of the reduced anatase TiO2 and its visible light photoactivity. The study is emphasized on the O vacancy, including the components of the defect states, the relationship with the bulk states and the way in which these electrons occupying the defect states are distributed in the real space. We find that the origin of the visible light photoactivity should be due to the transition of the excited electrons from the defect states sigma subscript g orbital to the sigma subscript u orbital in the upper conduction bands, rather than arising from the reduction of the band gap. The calculated results indicate that the localized defect states induced by the neutral and doubly ionized oxygen vacancies are all located in the band gap.